Interpretation of Constellations in the Ilmi Interpretation of the Ministry of Religion and Its Implications for the Development of Astronomy and Astrology - Laili Nur Hidayah; Salamah Noorhidayati (Jurnal Ushuluddin, 2022)
The Quran's concern for the natural order is evident through its verses. By studying verses about nature, humans can increase knowledge and include science in analyzing the content of the Quran, as the Ilmi interpretation issued by the Ministry of Religion interprets the kauniyah verses in the Qur'an using scientific findings. This article aims to discuss the Qur'an's insight into constellations, especially the function of constellations based on the interpretation of Ilmi which was launched by the Ministry of Religion and implied by the development of astronomy and astrology. This research is included in the category of literature research with the Ministry of Religion's Ilmi interpretation as the primary source and uses the maudhu'I method with the type of Ilmi interpretation. There are three verses out of the 13 verses that have been analyzed based on the term An-Najm. Concluding using inductive methods. The results of this study show that there are 3 constellation functions based on the interpretation of the Ministry of Religion's Ilmi interpretation, namely functioning as a directional direction, determining seasons, and determining time. The three functions are related to the development of astronomy and astrology. Astronomy can produce new findings through the three constellation functions, namely sextants and astrolabes. Meanwhile, astrology only utilizes the function of constellations as a determinant of seasons by using Javanese astrology, which is known as prey institutions